2016
DOI: 10.18805/lr.v0iof.11300
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cry1Ac copy number in transgenic pigeonpeaplants using quantitative real time PCR.

Abstract: Copy number of Cry1Ac in transgenic pigeonpea plants was determined by quantitative real time PCR using Syber Green as fluorescence indicator. Gene specific primers designed to amplify relatively long amplicons (400 -600 bp), for Cry1Ac was used to increase specificity and sensitivity of Real time PCR. Estimated copy number in transgenic lines using realtime quantitative PCR and southern hybridization was correlated and found to be same i.e. single copy number. This study shows effectivness of real-time PCR me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…4A), Lanes 1-5). Similar results for Southern hybridization have been shown for Vigna mungo (Bhomkar et al, 2008), Cicer arietinum (Ghanti et al, 2011;Khatodia et al, 2014), Vicia faba (Hanafy et al, 2013) and Cajanus cajan (Jain et al, 2017) revealed stable integration of transgene into transgenic plant genome whereas no signal was recorded in non-transformed control (WT) plants.…”
Section: Southern Hybridization Analysissupporting
confidence: 78%
See 2 more Smart Citations
“…4A), Lanes 1-5). Similar results for Southern hybridization have been shown for Vigna mungo (Bhomkar et al, 2008), Cicer arietinum (Ghanti et al, 2011;Khatodia et al, 2014), Vicia faba (Hanafy et al, 2013) and Cajanus cajan (Jain et al, 2017) revealed stable integration of transgene into transgenic plant genome whereas no signal was recorded in non-transformed control (WT) plants.…”
Section: Southern Hybridization Analysissupporting
confidence: 78%
“…It was found that real-time PCR analysis was significantly correlated with Southern blot analysis and both showed single copy insertion in respective transgenic chickpea plants. Similarly, single copy insertion was observed in transgenic chickpea (Khatodia et al, 2014) and pigeonpea (Jain et al, 2017).…”
Section: Copy Number Comparison Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…For developing other transgenic lines mentioned in Table 2 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], the seeds were directly transferred to potted soil after co-cultivation, omitting the step of germinating in the presence of cefotaxime. For wheat and rice transformation, 200 µM acetosyringone was added to the bacterial suspension during co-cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of GC content of DNA has a significant effect on its Tm. Because the higher the percentage of GC content, the higher its Tm Jain et al (2017).…”
Section: Methodsmentioning
confidence: 99%